Stability and Hopf Bifurcation Analysis of Coupled Optoelectronic Feedback Loops - Gang Zhu; Junjie Wei (Abstract and Applied Analysis)
The dynamics of a coupled optoelectronic feedback loops are investigated. Depending on the coupling parameters and the feedback strength, the system exhibits synchronized asymptotically stable equilibrium and Hopf bifurcation. Employing the center manifold theorem and normal form method introduced by Hassard et al. (1981), we give an algorithm for determining the Hopf bifurcation properties.